INFLUENCE OF INOCULUM DENSITY OF ROOT-KNOT NEMATODE [Meloidogyne incognita (Kofoid and White) Chitwood] AND PLANT AGE ON YIELD OF AMPALAYA (Momordica charantia L.) - Salares, F.A.; Gapasin, R.M. (Annals of Tropical Research, 1991)
A pot experiment was conducted to determine the most susceptible stage of growth of ampalaya, Momordica charantia L. to the root-knot nematode, Meloidogyne incognita infestation and the inoculum density of the nematode that could affect the yield. Gall and egg mass indices and nematode population recovered from the roots and soil were significantly higher in 2- and 4-wk old plants compared with 6- and 8-wk old plants regardless of inoculum density. Likewise, plants inoculated earlier had heavier root weight compared with plants inoculated at later stage but not the fresh weight of vines. Fresh root and vine weight were generally heavier at inoculum density of 20.000 compared with the T other inoculum density regardless of age of the plants. Total fruit yield of 2-and 4-wk old plants inoculated with 1,000 and 5,000 eggs were reduced by 68 to 70% and increased to 81 to 82% when inoculum density was increased to 10,000 and 20,000, respectively. Percent yield reduction was lower on 8-wk old plants regardless of inoculum density compared with 2-, 4-and 6-wk old plants, however, percent yield reduction at this growth stage increased as inoculum density was increased. Interaction effects of inoculum density versus age of plant on the production of galls and egg masses, fresh vine weight and weight of marketable and non-marketable fruits were significant.